Neurons with GABAergic phenotype in the visual system of Drosophila1. Issue 1 (22nd November 2012) - Raghu, Shamprasad Varija; Claussen, Jing; Borst, Alexander
Abstract The visual system of Drosophila contains ∼60, 000 neurons per hemisphere that are organized in parallel, retinotopically arranged columns. The neuroanatomy of these neurons has been mapped in considerable detail at both the light and ultrastructural level. However, studies providing direct evidence for synaptic signaling and the neurotransmitter used by individual neurons are relatively sparse. Here we characterize those neurons in the Drosophila optic lobes that possibly release gamma aminobutyric acid (GABA), the major inhibitory neurotransmitter of the insect central nervous system. We identified 26 different types of neurons of the lamina, medulla, lobula, and lobula plate. Based on the previous Golgi‐staining analysis (Fischbach and Dittrich [1989] Cell Tissue Res 258:441–475), the identified neurons are further classified into 11 major subgroups representing lamina monopolar (L), medulla intrinsic (Mi, Mt), bushy T (T), transmedullary (Tm), transmedullary Y (TmY), Y, lobula‐complex intrinsic (Lccn), lobula columnar (Lcn), lobula plate intrinsic (Lpi), and lobula tangential (Lt) cell types. This detailed map of neurons with GABAergic phenotype will contribute to the future neurogenetic dissection of information processing circuits in the fly visual system. J. Comp. Neurol. 521:252–265, 2013. © 2012 Wiley Periodicals, Inc.